2020
DOI: 10.1186/s40168-020-00932-8
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial function and genital inflammation in young South African women at high risk of HIV infection

Abstract: Background Female genital tract (FGT) inflammation is an important risk factor for HIV acquisition. The FGT microbiome is closely associated with inflammatory profile; however, the relative importance of microbial activities has not been established. Since proteins are key elements representing actual microbial functions, this study utilized metaproteomics to evaluate the relationship between FGT microbial function and inflammation in 113 young and adolescent South African women at high risk of HIV infection. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…The protonated form of LA predominates at a pH below its acid dissociation constant ( pKa 3.86) and possesses virucidal and anti-inflammatory activity, in contrast to the lactate anion that predominates at pH > 3.86 [ 38 , 41 , 42 ]. These data, and others [ 29 , 44 , 45 ], indicate that metabolites produced by optimal FRT microbiota species are likely key mediators of the health benefits associated with Lactobacillus -dominant microbiota.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…The protonated form of LA predominates at a pH below its acid dissociation constant ( pKa 3.86) and possesses virucidal and anti-inflammatory activity, in contrast to the lactate anion that predominates at pH > 3.86 [ 38 , 41 , 42 ]. These data, and others [ 29 , 44 , 45 ], indicate that metabolites produced by optimal FRT microbiota species are likely key mediators of the health benefits associated with Lactobacillus -dominant microbiota.…”
Section: Introductionsupporting
confidence: 64%
“…Lateral vaginal wall swabs were collected by the study nurse by rotating Dacron swabs 360° on the lateral vaginal wall before being placed in 1 ml phosphate-buffered saline (PBS), transported to the laboratory at 4° C and stored at −80 °C. Samples were computational randomised and the eluted material subjected to metaproteomic analysis using liquid chromatography-tandem mass spectrometry (LC-MS/MS) on a Q-Exactive quadrupole-Orbitrap MS (Thermo Fisher Scientific, MA, USA) coupled with a Dionex UltiMate 3000 nano-UPLC system (120 min per sample) [ 45 ]. Proteomic data were used to infer vaginal microbiome composition and host secretome as described previously [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted key functional pathways in the normal microbiota were peptidoglycan biosynthesis, phosphatidylglycerol biosynthesis I and II, peptidoglycan biosynthesis IV and pyrimidine nucleotide salvage pathways. Increased cell wall organization and peptidoglycan biosynthesis in Lactobacillus dominated microbiomes have been associated with reduced FGT inflammation ( Alisoltani et al., 2020 ) and in modulating the immune system ( Song et al., 2018 ). Peptidoglycan biosynthesis IV and pyrimidine nucleotide salvage pathways have been further described during the proliferative phase of menstrual cycle and associated with increased bacterial proliferation ( Chen et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The author reported that Additional file 2 for this article [1] is a draft copy of Additional file 1. The correct additional file 2 should have been an excel file.…”
Section: Supplementary Informationmentioning
confidence: 99%